Corynoneura Winnertz (Diptera, Chironomidae, Orthocladiinae) from Zhejiang Province, China - Fu, Yue; Wang, Xin-Hua; Fang, Xiang-Liang; Xiao, Yun-Li; Fu, Jun; Lin, Xiao-Long (Zootaxa, 2020)
The genus Corynoneura Winnertz, 1846 from Zhejiang Province in Oriental China is reviewed. Corynoneura aggeris Fu, sp. n., Corynoneura lateralis Fu, sp. n., Corynoneura petitspectabilis Fu, sp. n., Corynoneura prolata Fu, sp. n., and Corynoneura recta Fu, sp. n. are described and illustrated based on adult males. Corynoneura lobata Edwards, 1924 and Corynoneura tokarapequea Sasa et Suzuki, 1995 are redescribed and illustrated based on newly collected material. A key to known adult males of Corynoneura from Zhejiang Province is given.